The specifics of the corporate model of local self-government and the divergence of modern approaches to self-government at the local level in the Commonwealth countries - A. Larichev (Правоприменение, 2018)
The subject of the article is models of local self-government in Commonwealth countries.The purpose of this article is to substantiate or refute the hypothesis post-corporate model of local self-government is evolved.Methods of theoretical analysis are used, as well as legal methods, including the formal legal method and the method of comparative law.The main results and scope of their application. The corporate model of local government can be characterized by the following features: the lack of full constitutional recognition of local government as an independent form of public authority; formal institutional autonomy of municipal units as public (private-public) corporations of a special type that are not included into the system of state power; limited functional autonomy; lack of constitutional recognition of citizens’ or local communities’ right(s) to local self-government; limited accountability of local governments to the population, including the lack of sufficient legislative guarantees for the election of local authorities. These characteristics, grounded also in the historical specificity of local government development in Great Britain and its colonies, as well as in peculiarities of development of municipal units’ status in English law, are determined by the corporate character of municipal government, which does not arise from the power of communities, but is formed by the state "from above". The author also analyzes the differences in approaches to regulation and organization of local government in the Commonwealth countries.Overcoming the historical heritage, laid by the genesis of municipal corporations, in a number of Commonwealth states, indicates the formation of a new, post-corporate model of local government, which can be characterized by some features: the establishment of constitutional autonomy of local government as a special form of public power, its development as a form of democracy with greater control over the forms of self-government and governance at the local level by the population, as well as the establishment of a link between self-government and the local community. The proposed analysis may become a crucial point for future research in the field of post-corporate model of local self-government.Conclusions. Such countries as Australia and Ireland can presently be considered in a state of transition to the post-corporate model of local self-government.